Safety and Effectiveness of Essential Phospholipids Paste in Patients with Non-alcoholic Fatty Liver Disease or Viral Hepatitis - Ivashkin, Vladimir T.; Maev, Igor V.; Pavlov, Chavdar S.; Mayevskaya, Marina V.; Samsonov, Aleksey A.; Palgova, Lyudmila K.; Starostin, Kirill M. (Turkish Journal of Gastroenterology, 2021)
Background: Essential phospholipids (EPL) are used as adjuvant treatment in people with fatty liver disease and other chronic liverdiseases. A new formulation of EPL paste was developed to improve patient compliance. The study was aimed to assess the safety,patient-reported outcomes, and impact on compliance of the new EPL paste formulation in patients with non-alcoholic fatty liver disease(NAFLD) or viral hepatitis.Methods: The study enrolled 147 patients (48.3% male; mean ± standard deviation (SD) age 44.8 ± 10.5 years) in the intention-to-treatpopulation; 72.8% had NAFLD and 27.9% had viral hepatitis B (HBV) or hepatitis C (HCV). Patients received EPL paste (one 600 mgsachet 3 times daily) for 12 weeks, with 4-, 8-, and 12-week scheduled visits and a 13-week follow-up visit. Patient-reported outcomeswere evaluated at 4, 8, and 12 weeks compared with baseline using dedicated Likert scales. Compliance was assessed by comparingactual versus prescribed dosing of the EPL.Results: After 12-week treatment with EPL paste, statistically significant improvements were observed in mean ± SD Global OverallSymptom scores (from 4.21 ± 1.09 to 1.87 ± 0.91; P < .01) and overall Gastrointestinal Symptom scores (from 19.91 ± 5.74 to 11.17 ± 3.57;P < .01), compared to baseline scores. Compliance with prescribed essential phospholipid treatment was 99% throughout the 12-weektreatment period.Conclusion: Essential phospholipids paste had a favorable safety profile associated with improved gastrointestinal symptoms and withhigh levels of compliance in patients with NAFLD and viral hepatitis.